IoT monitoring for PV system optimization in hospital environment application - Andi, Kemas; Kusumanto, Raden; Yusi, Syahirman (Goodwood Publishing, 2024)
Purpose: This study aims to implement an Internet of Things (IoT)-based monitoring system to optimize photovoltaic (PV) system performance and ensure uninterrupted power supply for critical medical equipment, specifically ventilators and monitors, in the ICU room of RSI Siti Khadijah Palembang. Methodology/approach: The system uses on-grid solar panels connected to an Arduino-based IoT monitoring platform. The IoT system receives inputs from current and voltage sensors, enabling real-time supervision of solar panel output, battery status, and inverter performance. Automatic Transfer Switch (ATS) technology ensures seamless switching between PV and utility sources during periods of insufficient solar energy. Results/findings: The installed system demonstrates stable daily performance, with peak energy production reaching up to 400 Wp under optimal conditions. Real-time data from the IoT dashboard enables informed decision-making to maintain power supply continuity in the ICU. Voltage levels remained within a safe range for ICU operations throughout the test period. Conclusion: IoT integration enhances the reliability of hospital-based PV systems. The system proved effective in maintaining continuous energy delivery to life-saving equipment, reducing reliance on conventional UPS systems. Limitations: The current system lacks MPPT (Maximum Power Point Tracking) and thermal regulation, which could further optimize energy conversion efficiency under varying weather conditions. Contribution: This study provides a replicable model of IoT-enhanced PV deployment in hospital settings, offering valuable insights for renewable energy applications in critical infrastructure across tropical developing countries.